The Effect of Congestion on Productivity in the Semarang Urban Area - Khoirunni'mah, Annissa; Brilianti, Dani Fitria (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Traffic congestion in Semarang City has become a significant issue that impacts the productivity of individuals and businesses. This study aims to assess the effects of traffic jams on work efficiency, stress levels, and transportation costs, as well as to evaluate public perceptions of the adequacy of current transportation infrastructure and policies. A quantitative research approach was used, with data collected through a survey involving 172 respondents from various sectors, including administration, manufacturing, and retail trade. The survey assessed factors such as delays, stress, fatigue, and increased operational costs resulting from traffic congestion. The results showed that a majority of respondents reported being late for work due to traffic jams, with 56.98% strongly agreeing with this statement. Additionally, 52.91% of respondents indicated that the time spent in traffic jams negatively impacted their work productivity. Traffic congestion was also found to increase transportation costs, particularly fuel expenses, as confirmed by 52.91% of the respondents. The survey also revealed widespread support for the development of public transportation to alleviate congestion, with 72.09% of respondents in favor of such initiatives. The findings suggest that traffic congestion has a significant negative impact on productivity and economic growth, emphasizing the need for improved infrastructure and effective traffic management policies. The study provides valuable insights for local authorities and stakeholders in designing strategies to address congestion and promote a more efficient and sustainable transportation system in Semarang.